Sustainable Entrepreneurship: The Potential of Campus Waste in Making Entrepreneurial Products with High Selling Value - Novembrianto , Rizka; Mirwan, Mohamad; Ervina, Dea Febrica; Sholikhah, Mar'atus; Wicaksono, Pandu (Future Science, 2023)
UPN